Infectious diseases in the neonatal period: A literature review - Carrêro , Mair Luce Figueredo Porto; Souza, Maria Carolina Lopes de; Oliveira, Lorena Queiroz de; Alves, Marinelson Paulo; Matos, Maria de Lourdes Ferreira Medeiros de; Matos, Alcemar Antônio Lopes de; Carrêro, Josemar Simoes; Manhães, Martha Borges Neves (Seven Editora, 2024)
Neonatal infectious diseases are pathologies that affect newborns, usually in the first four weeks of life. They are transmitted through breastfeeding or during pregnancy. They are congenital when transmission occurs transplacentally. An example of this is cytomegalovirus, toxoplasmosis, syphilis, and rubella, acquired during childbirth (less than 48 hours of life), caused by group B Streptococcus and Escherichia coli or nosocomial (more than 48 hours of life) caused by acquisition during the period of stay in the Neonatal Intensive Care Unit due to healthcare-associated infections (HAI). In this context, the study aims to highlight the main infections that occur in the neonatal period, understand the pathogenic process, clinical manifestations, diagnosis, and treatment of infectious diseases. The methodology used was an exploratory literature review, with a qualitative approach, through bibliographic research of books and articles, using the Lilacs, PubMed and SciELO databases. Examples of this class of pathologies include early or late neonatal sepsis and viral infections such as neonatal herpes, hepatitis B, HIV, Zika, Chikungunya and dengue. Thus, it is concluded that a rapid diagnosis and treatment is important, as these infections evolve to severe conditions due to the immaturity of the neonate’s immune system. Prevention includes proper prenatal care, maternal immunization, and hygiene precautions during childbirth and after birth. DOI:https://doi.org/10.56238/sevened2023.007-089